Using the theory of combinations at the modeling of land plots exchange in agricultural land masses - Malashevskyi, М.; Malashevska, О. (Land Management, Cadastre and Land Monitoring, 2023)
The problem of land reallotment modeling in agricultural land masses aiming at land consolidation is scrutinized in the article. The topicality of the research is predefined by the need for the optimization of the structure of land tenure within an agricultural land mass, the implementation of measures on land consolidation. The research is aimed at the substantiation of the theory of combinations aiming at the improvement of the exchange of land plots, i.e.  the choosing of alternative land plots within an agricultural land mass. The calculations are based on choosing the land plots to be exchanged to provide the optimal for agricultural activities spatial characteristics of land plots. The calculation of the variants of the formation of the consolidated land tenure by a land owner who has the right to own the prevailing share of a typical agricultural land mass has been suggested. The results of the research can be used at the realization of complex and individual land consolidation projects; at the optimization of land tenure by the sublease of land plots; as a material  for the substantiation of the decision making on the land tenure optimization by territorial communities; in the following research on spatial land tenure and land ownership spatial improvement.
Keywords: combinations theory; land consolidation; land plots exchange; land reallotment; mathematical modeling